1991
DOI: 10.1210/jcem-72-1-96
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Free Fatty Acid Metabolism in the Pathogenesis of Insulin Resistance in Obesity and Noninsulin-Dependent Diabetes Mellitus*

Abstract: To investigate the mechanisms of insulin resistance in obesity and noninsulin-dependent diabetes mellitus (NIDDM), we examined oxidative and nonoxidative pathways of free fatty acid (FFA) and glucose metabolism in 14 lean and 17 obese (with normal oral glucose tolerance) nondiabetic subjects and in 8 lean and 8 obese subjects with NIDDM. FFA and glucose metabolism were measured using the sequential insulin clamp technique in combination with indirect calorimetry and infusion of [3-3H]glucose and [1-14C]palmita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
166
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(188 citation statements)
references
References 36 publications
18
166
1
3
Order By: Relevance
“…Furthermore, in this condition, hepatic insulin resistance is usually more severe and results in absolute glucose overproduction [52]. However, the NEFA turnover rate and total lipid oxidation have been reported to be only mildly abnormal in non-obese type 2 patients and in first-degree relatives of diabetic patients [53,54]. In non-diabetic patients with liver cirrhosis, basal endogenous glucose production is normal and is normally suppressed by insulin; skeletal muscle is insulin resistant because of reduced glycogen formation [55,56], whereas glucose oxidation has been found to be normal in the basal state and after insulin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this condition, hepatic insulin resistance is usually more severe and results in absolute glucose overproduction [52]. However, the NEFA turnover rate and total lipid oxidation have been reported to be only mildly abnormal in non-obese type 2 patients and in first-degree relatives of diabetic patients [53,54]. In non-diabetic patients with liver cirrhosis, basal endogenous glucose production is normal and is normally suppressed by insulin; skeletal muscle is insulin resistant because of reduced glycogen formation [55,56], whereas glucose oxidation has been found to be normal in the basal state and after insulin administration.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] From a metabolic point of view, it can be speculated that the greater reactivity might result in increased FFA production in subjects born SGA, increasing thereby the circulating FFA known to be deleterious in the control of insulin sensitivity. 11,12 Furthermore, regarding the interplay between insulin and catecholamines in the adipocyte lipolytic regulation, it has been shown that the magnitude of the lipolytic effect induced by catecholamines overrides the antilipolytic effect of insulin. 30,31 This is clearly evidenced in the present study by the pattern of glycerol production in the two probes.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the adipose tissue in the pathophysiology of insulin resistance is mostly based on its lipolytic activity, resulting in free fatty acids (FFA) production and mobilization, 11,12 which has been largely documented to be deleterious on glucose utilization and insulin action. 12,13 In humans, insulin and catecholamines are the major hormonal regulators of the lipolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,13,27,28 Altered LCFA disposition is typical of both obesity and NIDDM. 29,30 Indeed, some believe that such changes are the primary disturbances in these conditions. [31][32][33][34] Animal models have been very useful in studying this process.…”
Section: Discussionmentioning
confidence: 99%